Numerical evaluation of the long-term behavior of precast continuous bridge decks - Carlos Sousa (2012)
Continuous bridge decks constructed with precast girders undergo significant stress changes caused by the concrete delayed deformations because of creep and shrinkage. These effects must be taken into account in the design of new structures. The validation of the analysis procedures should ideally be carried out through the comparison between the calculations and the results observed in real structures. However, experimental results of the construction and long-term behavior of these structures are scarce. The construction of a major bridge in Portugal has provided the opportunity to monitor one such structure. This paper presents the monitoring campaign and the analysis strategy that was developed to assess the long-term variation of strains and stresses in precast continuous bridges. The numerical analysis was validated by comparison with the results observed in the real bridge. The consequences of carrying out simplified analyses based on limited information about the concrete properties and the construction sequence are also evaluated.